AWARENESS ON ORAL HEALTH AND HYGIENE AMONG ELDERLY PATIENTS IN INDIAN POPULATION - A SURVEY - B, Revathi.; R, Gayathri .; Priya, V.Vishnu (International Journal of Psychosocial Rehabilitation, 2020)
To create awareness on oral hygiene among elderly patients in South Indian population.Oral hygiene is associated with health related quality of life that impact the general well- being of an individual in physical, mental and social domains. Approximately 68% of the adults aged 65 years or above have periodontitis. Hence dental care is considered to be the essential contributing factor to experience a healthy life in elderly and prevent general health complications. In this survey there were 100 participants in which all of them were elderly patients aged 50 years or above. It is a questionnaire based online survey. 17 questions were asked related to oral hygiene using survey planet.About 50% of the participants were not able to eat all kinds of foods which they like and 52.3% of the participants are not comfortable with all kinds of food they eat. About 34.2% of them lost mainly molars and premolars. As they are used for mastication predominantly followed by anterior teeth(19.3%).About 27.3% of them consulted a dentist, 45.5% of them took self remedies and the remaining 27.3% of them did not take any measures. Fear and expense were the main excuse for not taking any measures. About 13.6% of the patients accepted that they don’t show any kind of interest towards taking a treatment.About 71.6% of the elderly population accept that they do not have enough knowledge about the oral hygiene. Professional health care services is low among elder people. Hence it is in the hands of dentists to create awareness about oral hygiene and importance of consulting a dentist at equal intervals. Dentist must initiate to provide treatment in a good quality as well as at low expense. So that they come forward to take up the treatment.